Antibacterial coating, preparation method thereof and application of antibacterial coating in DUWLs pipeline

By applying an antibacterial coating composed of polydopamine, sulfobetaine methacrylate and nanosilver to the inner wall of the DUWLs pipeline, the problems of bacterial proliferation and biofilm formation in the DUWLs pipeline are solved, achieving efficient antibacterial effects and reducing disinfectant corrosion.

CN119708593APending Publication Date: 2025-03-28SHANGHAI XUHUI DISTRICT DENTAL HOSPITAL (SHANGHAI XUHUI DISTRICT DENTAL DISEASE CONTROL & PREVENTION INSTITUTE) +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411672799.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Bacteria in DUWLs pipelines are easy to colonize and proliferate, forming biofilms, and commonly used chemical disinfectants can cause corrosion and health risks to pipeline components, making it difficult to completely solve the problem of bacterial contamination.

Method used

An antibacterial coating, including polydopamine (PDA), sulfobetaine methacrylate (SBMA) and nanosilver (AgNPs), was used to inhibit bacterial proliferation and protein adsorption by specific preparation methods.

Benefits of technology

This antibacterial coating can effectively inhibit the proliferation of bacteria in the DUWLs pipeline, prevent the formation of biofilms, and the antibacterial rate of Staphylococcus aureus and E. coli reaches 100%, while reducing the erosion and damage of the pipeline by disinfectants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708593A_ABST
    Figure CN119708593A_ABST
Patent Text Reader

Abstract

The invention discloses an antibacterial coating and a preparation method and application thereof in DUWLs pipelines, and relates to the technical field of medical materials, the antibacterial coating comprises PDA, SBMA and AgNPs; the antibacterial coating has high protein adsorption resistance, and adsorption of protein in the DUWLs pipeline can be effectively inhibited; the antibacterial coating has a good antibacterial effect and can effectively inhibit the proliferation of bacteria in the DUWLs pipeline and prevent the formation of a biological membrane; the antibacterial rate to staphylococcus aureus and escherichia coli reaches 100%, the bacterial form is incomplete, and cytoplasm leaks; meanwhile, the antibacterial coating can reduce erosion damage of the disinfectant to the DUWLs pipeline, and the antibacterial coating has important application value for solving the problem of DUWLs pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical materials, and in particular to an antibacterial coating and a preparation method thereof and application thereof in DUWLs pipelines. Background Art

[0002] Dental Unit Waterlines (DUWLs) are a set of complex, interconnected thin-diameter plastic pipes that supply water to all connected flushing and cooling devices, cup water inlets, and bowl-shaped flushing outlets. Their main function is to flush and cool during treatment. The internal structure of the dental unit is complex and difficult to disassemble and clean, and there is a problem that it is difficult to meet the disinfection standards. Therefore, an effective method is needed to solve the problem of bacterial contamination of DUWLs.

[0003] DUWLs have a small water flow rate. When not in use, the water flow is stagnant, and bacteria are easily colonized in the tube, further growing to form biofilms. In addition, the blood and saliva in the patient's mouth will be sucked back into the DUWLs, contaminating the machine's water path and also leading to the formation of biofilms. The pathogenic bacteria present on the inner wall of DUWLs mainly include Pseudomonas aeruginosa, Escherichia coli, Candida albicans, nontuberculous mycobacteria, etc. If DUWLs are not effectively sterilized, the risk of inflammation or allergic diseases in oral patients and medical staff will be significantly increased. Therefore, DUWLs should be properly cleaned and disinfected to minimize microbial contamination and meet water standards.

[0004] Common DUWLs disinfection methods include chemical disinfection and physical sterilization. The formation of biofilm can be inhibited by ultraviolet irradiation, filter installation and mechanical wiping, but because water pipes are narrow and complex, and microorganisms are easy to colonize on water pipes, it is difficult to completely remove attached bacteria by physical sterilization. In order to reduce the attachment and proliferation of DUWLs bacteria and prevent the formation of biofilm, the use of chemical disinfectants is a simple and effective method. Sodium hypochlorite, hydrogen peroxide, chlorhexidine, etc. are often used to clean water pipes. However, since chemical disinfectants can cause corrosion and damage to DUWLs pipeline components, and some chemical disinfectants will cause certain risks to health as the concentration increases, chemical disinfection is not the optimal method for sterilization. Therefore, giving DUWLs pipelines safe and effective antibacterial ability is the current direction of water pipeline improvement and development. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an antibacterial coating and a preparation method thereof and an application in DUWLs pipes. The antibacterial coating can effectively inhibit the proliferation of bacteria in DUWLs pipes, reduce the adsorption of proteins, and at the same time reduce the erosion of DUWLs pipes caused by excessive use of disinfectants.

[0006] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0007] The first object of the present invention is to provide an antibacterial coating comprising polydopamine (PDA), sulfobetaine methacrylate (SBMA) and silver nanoparticles (AgNPs).

[0008] Furthermore, the mass percentage of the AgNPs in the antibacterial coating is 20-30%.

[0009] Furthermore, the mass percentage of the PDA in the antibacterial coating is 60-80%.

[0010] The second object of the present invention is to provide a method for preparing an antibacterial coating, comprising the following steps:

[0011] Step 1, activating polyurethane (PU) to obtain activated PU;

[0012] Step 2, immersing the activated PU in a DA solution, stirring, taking out, rinsing, and drying to obtain PU-PDA;

[0013] Step 3, immersing PU-PDA in SBMA solution, stirring, taking out, rinsing, and drying to obtain PU-PDA-SBMA;

[0014] Step 4: Soak PU-PDA-SBMA in a sealed container containing Tollens reagent, take it out, rinse it, and dry it to obtain PU-PDA-SBMA-Ag.

[0015] Furthermore, the activation treatment in step 1 is carried out in a low-temperature plasma treatment machine with an oxygen flow rate of 10 to 30 cm 3 / min, electrode power is 100~500W, and processing time is 1~10min.

[0016] In the present invention, oxygen-containing active groups are introduced on the surface of PU through activation treatment, which is beneficial to accelerate the polymerization of DA into PDA on the surface of PU.

[0017] Furthermore, the DA solution in step 2 is prepared by mixing DA with tris buffer, wherein the concentration of DA is 1.5-2.5 mg / mL, and the pH value of tris buffer is 8.3-8.7.

[0018] Furthermore, the stirring temperature in step 2 is 20 to 30° C., and the stirring time is 12 to 24 hours.

[0019] In the present invention, DA generates PDA in situ on the surface of PU through self-polymerization, and PDA has high adhesion and excellent biocompatibility and low toxicity.

[0020] Furthermore, the SBMA solution in step 3 is prepared from SBMA, water, ethanol and triethylamine, wherein the concentration of SBMA is 0.08-0.085 g / mL, and the volume ratio of water, ethanol and triethylamine is (795-805):(155-165):(2-4).

[0021] Furthermore, the stirring temperature in step 3 is 50-60° C. and the stirring time is 12-24 h.

[0022] In the present invention, SBMA has good anti-protein nonspecific adsorption properties, which helps to reduce waterway pollution caused by protein adsorption accumulation.

[0023] Furthermore, the rinsing in step 2 and step 3 is repeated rinsing with deionized water and ethanol.

[0024] Furthermore, the drying in step 2 is oven drying at a drying temperature of 50 to 60°C.

[0025] Furthermore, the drying in step 3 is nitrogen drying, and the drying temperature is 20-30°C.

[0026] Furthermore, the concentration of the Tollens reagent in step 4 is 9.8-10.2 mg / mL.

[0027] Tollens reagent, i.e., silver ammonia solution, utilizes the reducing property of polydopamine (PDA) to reduce the silver ions in Tollens reagent into silver nanoparticles, while the adhesiveness of PDA itself helps to fix the silver nanoparticles on the coating surface.

[0028] The third object of the present invention is to provide application of the antibacterial coating in DUWLs pipes.

[0029] DUWLs pipes are usually made of PU material, which has the characteristics of high strength, wear resistance, corrosion resistance and pressure resistance. The preparation method of the antibacterial coating of the present invention can be applied to the inner wall of the DUWLs pipe to form an antibacterial coating.

[0030] The beneficial effects of the present invention are:

[0031] (1) The antibacterial coating of the present invention has a strong ability to resist protein adsorption and can effectively inhibit the adsorption of proteins in DUWLs pipelines.

[0032] (2) The antibacterial coating of the present invention has a good antibacterial effect, can effectively inhibit the proliferation of bacteria in DUWLs pipelines, and prevent the formation of biofilms; the antibacterial rate against Staphylococcus aureus and Escherichia coli reaches 100%, and the bacterial morphology is incomplete and the cytoplasm is leaked.

[0033] (3) The antibacterial coating of the present invention can reduce the erosion and damage of disinfectants to DUWLs pipelines, and has important application value in solving the DUWLs pollution problem. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Optical images of PU (A), PU+O2 (B), PU-PDA (C), PU-PDA-SBMA (D) and PU-PDA-SBMA-Ag (E) films in Example 1;

[0035] Figure 2 SEM images of PU (A), PU+O2 (B), PU-PDA (C), PU-PDA-SBMA (D) and PU-PDA-SBMA-Ag (E) films in Example 1;

[0036] Figure 3 FTIR spectra of PU, PU+O2, PU-PDA, PU-PDA-SBMA and PU-PDA-SBMA-Ag films in Example 1;

[0037] Figure 4 The SEM images, EDS images and relative element contents of the PU-PDA-SBMA (A, C) and PU-PDA-SBMA-Ag (B, D) films in Example 1;

[0038] Figure 5 The water contact angles of the PU (A), PU+O2 (B), PU-PDA (C), PU-PDA-SBMA (D) and PU-PDA-SBMA-Ag (E) films in Example 1;

[0039] Figure 6 AFM images of PU (A), PU+O2 (B), PU-PDA (C), PU-PDA-SBMA (D) and PU-PDA-SBMA-Ag (E) films in Example 1;

[0040] Figure 7 The fluorescence qualitative analysis and BSA UV quantitative analysis results of the anti-protein adsorption of PU, PU+O2, PU-PDA, PU-PDA-SBMA and PU-PDA-SBMA-Ag films in Example 1;

[0041] Figure 8The antibacterial ability test results of PU (A), PU+O2 (B), PU-PDA (C), PU-PDA-SBMA (D) and PU-PDA-SBMA-Ag (E) films against Escherichia coli in Example 1;

[0042] Fig. 9 The antibacterial ability test results of PU (A), PU+O2 (B), PU-PDA (C), PU-PDA-SBMA (D) and PU-PDA-SBMA-Ag (E) films in Example 1 against Staphylococcus aureus;

[0043] Fig.10 The antibacterial performance test results of PU, PU+O2, PU-PDA, PU-PDA-SBMA and PU-PDA-SBMA-Ag films against Escherichia coli and Staphylococcus aureus in Example 1;

[0044] Fig.11 The effects of PU, PU+O2, PU-PDA, PU-PDA-SBMA and PU-PDA-SBMA-Ag films in Example 1 on the bacterial activity of Escherichia coli and Staphylococcus aureus;

[0045] Fig.12 The effects of PU (1), PU+O2 (2), PU-PDA (3), PU-PDA-SBMA (4) and PU-PDA-SBMA-Ag (5) films in Example 1 on the morphology of Escherichia coli and Staphylococcus aureus. DETAILED DESCRIPTION

[0046] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0047] The PU in the following examples was purchased from Lubrizol Corporation ( 8663-85A).

[0048] Preparation Example 1

[0049] Step 1: Place the PU film in a low-temperature plasma treatment machine for activation for 5 minutes with an oxygen flow rate of 20 cm 3 / min, the electrode power is 200W, and PU+O2 film is obtained.

[0050] Step 2: Immerse the PU+O2 film in a mixed solution prepared by 80 mg DA and 40 mL tris buffer (pH = 8.5), stir at room temperature for 24 h, take it out and rinse it repeatedly with deionized water and ethanol, and dry it in an oven at 50°C to obtain a PU-PDA film.

[0051] Step 3, prepare 20 mL of a mixed solution consisting of ultrapure water, ethanol and triethylamine, wherein the volume ratio of ultrapure water, ethanol and triethylamine is 800:160:3, immerse the PU-PDA film in the mixed solution, add 1.64 g SBMA, stir at 55 ° C for 24 hours, take out and rinse repeatedly with deionized water and ethanol, and dry with nitrogen at 25 ° C to obtain a PU-PDA-SBMA film.

[0052] Step 4: Soak the PU-PDA-SBMA film in a sealed flask containing Tollens reagent (10 mg / mL) for 0.5 h, take it out, rinse it, and dry it in an oven at 40° C. to obtain a PU-PDA-SBMA-Ag film.

[0053] Depend on Figure 1 It can be seen that the color depth of PU, PU+O2, PU-PDA, PU-PDA-SBMA and PU-PDA-SBMA-Ag films all change to varying degrees.

[0054] Depend on Figure 2 It can be seen that Example 1 prepared a uniform and stable coating on the surface of the PU film.

[0055] Depend on Figure 3 It can be seen that compared with the PU-PDA film, the PU-PDA-SBMA-Ag film has a -1 and 1041cm -1 New peaks appeared at , which belonged to the S=O asymmetric stretching and S=O symmetric stretching of the SBMA functional group, respectively, which proved that SBMA was successfully loaded on PU-PDA.

[0056] from Figure 4 It can be seen that the surfaces of both PU-PDA-SBMA and PU-PDA-SBMA-Ag films contain S element, and the atomic percentage of Ag in the PU-PDA-SBMA-Ag film increases, which proves the successful synthesis of PU-PDA-SBMA-Ag.

[0057] from Figure 5 It can be seen that compared with PU, PU+O2, PU-PDA and PU-PDA-SBMA films, PU-PDA-SBMA-Ag film has the smallest contact angle and the strongest hydrophilicity.

[0058] from Figure 6 It can be seen that the surface roughness of PU-PDA-SBMA-Ag film is the largest compared with PU, PU+O2, PU-PDA and PU-PDA-SBMA films.

[0059] Preparation Example 2

[0060] The method of Example 1 was followed except that the oxygen flow rate in step 1 was 15 cm 3 / min, the electrode power is 300W.

[0061] Preparation Example 3

[0062] The method of Example 1 was followed, except that the mixed solution in step 2 was prepared from 100 mg DA and 50 mL tris buffer (pH=8.5).

[0063] Preparation Example 4

[0064] The method of Example 1 was followed, except that the amount of SBMA used in step 3 was 3.28 g.

[0065] Preparation Example 5

[0066] The method of Example 1 was followed, except that the PU-PDA-SBMA film in step 4 was immersed in the Tollens reagent for 1 h.

[0067] Application Example 1

[0068] Evaluation of anti-protein adsorption performance:

[0069] Using BSA as a model protein and labeled with fluorescent dye Cy5.5, the film prepared in Example 1 was tested for its anti-protein adsorption performance.

[0070] Take 16.7 mg Cy5.5 and 83.3 mg bovine serum albumin (BSA), stir at room temperature for 24 hours, then place the obtained BSA-Cy5.5 solution in a dialysis bag for dialyzing (molecular weight cutoff 5000), freeze-dry and seal, and place in a 4°C refrigerator for standby use. The PU, PU+O2, PU-PDA, PU-PDA-SBMA, and PU-PDA-SBMA-Ag films in Preparation Example 1 were incubated with the refrigerated BSA-Cy5.5 solution at 37°C for 4 hours, and the films were taken out after the incubation for fluorescence intensity detection, and the remaining solution was subjected to ultraviolet absorbance measurement to calculate the BSA adsorption amount.

[0071] Depend on Figure 7 It can be seen that the fluorescence intensity of PU, PU+O2, PU-PDA, PU-PDA-SBMA and PU-PDA-SBMA-Ag films gradually weakened, indicating that the protein adsorbed by the film gradually decreased and the anti-protein adsorption performance was enhanced; the UV quantitative results also showed that the protein content on the surface of the PU-PDA-SBMA-Ag film was the lowest. This shows that the PU-PDA-SBMA-Ag film in Preparation Example 1 has the strongest anti-protein adsorption performance.

[0072] Application Example 2

[0073] The antibacterial performance of the film prepared in Example 1 was evaluated:

[0074] The antibacterial properties of the films were evaluated using standard strains of Gram-negative Escherichia coli (E. coli, ATCC 25922) and Gram-positive Staphylococcus aureus (S. aureus, ATCC 25923). 6 CFU / mL, take 100μL of bacterial solution and spread it evenly on the plate, place a film sample of 1.5cm×1.5cm on the plate, put it in a 37℃ constant temperature incubator and culture it for 24h, take it out and observe whether there is an inhibition zone and the size of the inhibition zone.

[0075] from Figure 8 and Fig. 9 It can be seen that the PU-PDA-SBMA-Ag film in Preparation Example 1 has an antibacterial area, and the inhibition zone reaches 0.6-0.8 mm (Escherichia coli) and 1.4-2.8 mm (Staphylococcus aureus), which indicates that the PU-PDA-SBMA-Ag film has good antibacterial properties.

[0076] Application Example 3

[0077] The antibacterial performance of the film prepared in Example 1 was evaluated:

[0078] The antibacterial properties of the films were evaluated using Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus.

[0079] Antibacterial test 1:

[0080] The film was sterilized with 75% alcohol for 2 h and placed in a 24-well plate. 60 μL of the 10 7 CFU / mL of bacterial solution was inoculated on the surface of the film sample, placed in a 37℃ constant temperature incubator for 24 hours, and the bacterial solution was collected and diluted to 100 times. 100μL of the diluted bacterial solution was evenly spread on the surface of the agar plate, and the agar plate was inverted and placed in a 37℃ constant temperature incubator for 18 hours. The colonies on the surface of the agar plate were counted (GB / T 4789.2) and the antibacterial rate was calculated.

[0081] Antibacterial rate (%) = (AB) / A×100

[0082] Among them, A is the average number of colonies on the surface of the PU film, and B is the average number of colonies on the surface of the film in the test group.

[0083] from Fig.10It can be seen that PU-PDA, PU-PDA-SBMA and PU-PDA-SBMA-Ag films can inhibit the proliferation of Escherichia coli and Staphylococcus aureus, among which PU-PDA-SBMA-Ag film has the strongest inhibitory effect on the proliferation activity of Escherichia coli and Staphylococcus aureus.

[0084] Antibacterial test 2:

[0085] The film was sterilized with 75% alcohol for 2 h and placed in a 24-well plate. 60 μL of the 10 7 CFU / mL of bacterial solution was inoculated on the surface of the film, placed in a 37°C constant temperature incubator for 24 hours, rinsed twice with 500μL of saline, and then added with 500μL of alamarBlue solution diluted 10 times with saline for 2 hours. 100μL of the reaction solution was placed in a 96-well plate, and its fluorescence intensity was measured with an ELISA reader at an excitation wavelength of 560nm and an emission wavelength of 590nm.

[0086] from Fig.11 It can be seen that Escherichia coli and Staphylococcus aureus on the surfaces of PU, PU+O2, PU-PDA and PU-PDA-SBMA films have high bacterial activity, while the bacterial activity on the surface of PU-PDA-SBMA-Ag film is significantly reduced.

[0087] Antibacterial test three:

[0088] The film was sterilized with 75% alcohol for 2 h and placed in a 24-well plate. 60 μL of the 10 7 CFU / mL of bacterial liquid was inoculated on the surface of the film and cultured in a constant temperature incubator at 37°C for 24 hours. The film was rinsed twice with 500μL of normal saline and transferred to a new 24-well plate. 500μL of 2.5% glutaraldehyde solution was added to each well. The film was then gradiently dehydrated with ethanol solutions with volume fractions of 30%, 50%, 75%, 90%, 95% and 100%. The film was then placed in a mixed solution of ethanol and hexamethyldisilane (HMDS) (the volume ratios of ethanol to HMDS were 2:1, 1:1, and 1:2, respectively) and pure HMDS solution for dehydration. The dehydrated film was sprayed with gold (platinum) on the surface, and the bacterial morphology on its surface was observed using a scanning electron microscope.

[0089] from Fig.12It can be seen that the bacterial morphology of Escherichia coli and Staphylococcus aureus on the surface of PU, PU-PDA, PU-PDA-SBMA and PU-PDA-SBMA-Ag films has changed. Compared with PU, PU-PDA and PU-PDA-SBMA films, the number of bacteria on the surface of PU-PDA-SBMA-Ag film is significantly reduced, and the bacterial morphology is incomplete, indicating that PU-PDA-SBMA-Ag film has a good antibacterial effect.

[0090] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. An antibacterial coating, characterized in that: The antibacterial coating includes PDA, SBMA and AgNPs.

2. The antibacterial coating according to claim 1, characterized in that: The mass percentage of the AgNPs in the antibacterial coating is 20-30%.

3. The antibacterial coating according to claim 1, characterized in that: The mass percentage of the PDA in the antibacterial coating is 60-80%.

4. The method for preparing the antibacterial coating according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Step 1, activating PU to obtain activated PU; Step 2, immersing the activated PU in a DA solution, stirring, taking out, rinsing, and drying to obtain PU-PDA; Step 3, immersing PU-PDA in SBMA solution, stirring, taking out, rinsing, and drying to obtain PU-PDA-SBMA; Step 4: Soak PU-PDA-SBMA in a sealed container containing Tollens reagent, take it out, rinse it, and dry it to obtain PU-PDA-SBMA-Ag.

5. The method for preparing the antibacterial coating according to claim 4, characterized in that: The activation treatment in step 1 is carried out in a low-temperature plasma treatment machine with an oxygen flow rate of 10 to 30 cm 3 / min, electrode power is 100~500W, and processing time is 1~10min.

6. The method for preparing the antibacterial coating according to claim 4, characterized in that: The DA solution in step 2 is prepared from DA and tris buffer, wherein the concentration of DA is 1.5-2.5 mg / mL, and the pH value of the tris buffer is 8.3-8.

7.

7. The method for preparing the antibacterial coating according to claim 4, characterized in that: The SBMA solution in step 3 is prepared from SBMA, water, ethanol and triethylamine, wherein the concentration of SBMA is 0.08-0.085 g / mL, and the volume ratio of water, ethanol and triethylamine is (795-805):(155-165):(2-4).

8. The method for preparing the antibacterial coating according to claim 4, characterized in that: The concentration of the Tollens reagent in step 4 is 9.8-10.2 mg / mL.

9. The method for preparing the antibacterial coating according to claim 4, characterized in that: The stirring temperature in step 2 is 20 to 30° C. and the stirring time is 12 to 24 hours; Preferably, the stirring temperature in step 3 is 50-60° C. and the stirring time is 12-24 h; Preferably, the rinsing in step 2 and step 3 is repeated rinsing with deionized water and ethanol; Preferably, the drying in step 2 is oven drying at a drying temperature of 50 to 60° C. Preferably, the drying in step 3 is nitrogen drying at a drying temperature of 20 to 30°C.

10. Use of the antibacterial coating according to any one of claims 1 to 3 or the antibacterial coating prepared by the method for preparing the antibacterial coating according to any one of claims 4 to 9 in DUWLs pipelines.

Citation Information

Cited By

  • BNF-at bimetal MOF-based wave-absorbing corrosion-resistant composite coating and preparation method thereof

    CN120737691A